Rethinking pluralism : ritual, experience, and ambiguity - Seligman, Adam B., 1954- (Oxford University Press, 2012)
'Rethinking Pluralism' suggests a new approach to the problem of ambiguity and social order, which goes beyond the default modern position of 'notation' (resort to rules and categories to disambiguate). The book argues that alternative, more particularistic modes of dealing with ambiguity through ritual and shared experience better attune to contemporary problems of living with difference.